Special issue on software engineering for Connected Health: Challenges and research roadmap. Issue 7 (5th February 2018) - Carroll, Noel; Kuziemsky, Craig; Richardson, Ita
Abstract: Over the past decade, there have been increasing expectations and pressures placed on health care providers to deliver more efficient, quality, and safe health care services. As a result, this shifts the balance between supply‐and‐demand of health care services. It also brings about new challenges for health care professionals' capabilities to deliver safe and quality care in a timely manner. There are significant opportunities to exploit information and communications technology and transform how health care service is provided. Connected Health is one such transformation for health care management and changes in health care practice. However, the field of Connected Health is still in its infancy. This Special Issue in Software Engineering for Connected Health begins to address this and presents 5 quality contributions to demonstrate how software engineering research plays an important role in Connected Health research. These contributions also identify the limitations of the existing theories and to develop new or revised theories of Software Engineering for Connected Health.